Genomes of Geoalkalibacter ferrihydriticus Z-0531(T) and Geoalkalibacter subterraneus Red1(T), Two Haloalkaliphilic Metal-Reducing Deltaproteobacteria - Badalamenti, Jonathan P. (Genome Announc, 2015)
We sequenced and annotated genomes of two haloalkaliphilic Deltaproteobacteria, Geoalkalibacter ferrihydriticus Z-0531(T) (DSM 17813) and Geoalkalibacter subterraneus Red1(T) (DSM 23483). During assembly, we discovered that the DSMZ stock culture of G. subterraneus was contaminated. We reisolated G. subterraneus in axenic culture and redeposited it in DSMZ and JCM.